Behavioral impulsivity mediates the relationship between decreased frontal gray matter volume and harmful alcohol drinking: A voxel-based morphometry study. (December 2016) - Gröpper, Sonja; Spengler, Stephanie; Stuke, Heiner; Gawron, Christiane K.; Parnack, Jenny; Gutwinski, Stefan; Wiers, Corinde E.; Bermpohl, Felix
Abstract: Alcohol use disorder (AUD) with harmful drinking patterns is on the one hand characterized by impulsive behavior and is on the other hand known to involve structural brain alterations with lower gray matter volume (GMV), especially in the prefrontal cortex (PFC). So far it is unclear whether frontal brain volumes are associated to harmful alcohol drinking and impulsivity, while controlling simultaneously for a wide array of important confounding factors, which are related to alcohol consumption. We used voxel-based morphometry in 99 adults ranging within a continuum of normal to harmful drinking behavior and alcohol dependence, measured by the 'Alcohol Use Disorders Identification Test', to examine whether the severity of harmful drinking is correlated with structural markers, in particular in the PFC and whether such markers are linked to self-reported impulsivity. We included alcohol and nicotine lifetime exposure, age, education, and BMI as covariates to control that GMV decreases were not related to those factors. Harmful drinking was associated with lower GMV in the right frontal pole, left inferior frontal gyrus, and bilateral inferior parietal lobe. GMV loss in the PFC regions was correlated with increased impulsivity. Follow-up mediation analyses showed that the relationship between GMV in the frontal pole and harmful drinking was mediated by impulsivity. Our findings show that PFC reductions are associated with harmful drinking and impulsivity. Our data suggest that reduced frontal pole GM, independent of a number of alcohol drinking associated covariates, e.g. lifetime alcohol consumption, is related to impaired top-down control of alcohol drinking behavior. Highlights: Severity of harmful alcohol drinking is associated with multiple brain atrophies. PFC reductions are associated with harmful drinking and increased impulsivity. Impulsivity mediates frontal pole volume reduction and harmful drinking. PFC volume loss is not associated with covariates such as lifetime alcohol intake.